2005
DOI: 10.1007/s00531-005-0043-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of recent movement potentials in Schleswig-Holstein (Germany) by GIS-based calculation of correlation coefficients

Abstract: In order to investigate connections between deep tectonic and halokinetic structures and the development of recent topography, GIS-based calculation of correlation coefficients was carried out between different stratigraphic horizons of the deep Northwest German Basin (NGB) according to the ''Geotektonischer Atlas von NW-Deutschland'' and surface topography of Schleswig-Holstein. The results show seven areas of high correlation that are traceable from the Base Zechstein up to the recent surface topography. Fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Comparable observations from northern Germany were made by Reicherter et al (2005), Szeder & Sirocko (2005) and Lehné & Sirocko (2005) and, from Poland, by Kurzawa (2003) amongst others.…”
supporting
confidence: 60%
“…Comparable observations from northern Germany were made by Reicherter et al (2005), Szeder & Sirocko (2005) and Lehné & Sirocko (2005) and, from Poland, by Kurzawa (2003) amongst others.…”
supporting
confidence: 60%
“…-The fill of the Central European Basin System is characterized by a large number of salt structures. Comparable phenomena were shown by Lehn e & Sirocko (2005) in NW Germany and Al Hseinat et al (2016) for the Baltic Sea, where faulting and surface subsidence is related to ongoing movements along local graben structures and the rise of salt diapirs. Lang et al (2014) showed in their modelling study that salt structures can be reactivated by ice-loading.…”
Section: Deformation Structuresmentioning
confidence: 83%
“…At the beginning of this century, the area under consideration became of additional interest because seismic and well data were provided by the oil and gas industry through the German Society for Petroleum and Coal Science and Technology (DGMK) in frame of the DFG-SPP 1135 "Dynamics of sedimentary systems under varying stress conditions by example of the Central European Basin system". Based on these data, several results have been published concerning the structure and evolution of the GG with focus on salt tectonics (Maystrenko et al, 2005a, b), recent movements (Lehne & Sirocko, 2005), and thermal maturity (Rodon & Littke, 2005). In this paper, the evolution of salt structures of the GG has been studied backwards in time by means of 3D numerical modelling.…”
Section: Previous Work Data and Methodsmentioning
confidence: 99%